DEVELOPING VOCAL AND CHORAL SKILLS IN PRIMARY SCHOOL CHILDREN - Kenjebaeva, Sabira Saylauovna; Jumbayev, Ersayim Miyras uli (SCIENCE and SOCIETY, 2026)
The article considers methodological approaches and practical recommendations for the development of vocal and choral skills in children of primary school age. The physiological characteristics of the children’s voice, the psychological characteristics of the musical sensitivity of primary school students are analyzed. Based on existing musical pedagogical experiences, specific recommendations are given for the formation of singing posture, breathing, sound production, diction, ensemble and line, emotional-expressiveness in children aged 7-11.